IMPROVING FINANCIAL PERFORMANCE THROUGH PROBABILISTIC INVENTORY MANAGEMENT AND COST EFFICIENCY ANALYSIS: LEARN FROM A DAIRY MILK COOPERATIVE - Yunani, Akhmad; Firmialy, Sita (Jurnal Riset Bisnis dan Manajemen, 2025)
The study mainly focused on the inventory management of wheat pollard, the most essential material for the production of concentrates required by cooperative members. A probabilistic inventory management model is applied to address the issue of uncertainty in concentrates requirements. The model recommends a potential inventory cost savings. More precisely, the model suggests to order an amount of 60,000 kg of wheat pollard and transport using three trucks with the capacity of 20 tons respectively. As a consequence, the company save IDR32.63 million of inventory cost each year. In addition, the cooperative can meet nearly all requests for wheat pollard with a 98% service level. The study’s findings indicate that adopting the probabilistic inventory management model can enhance the financial performance of the cooperative through inventory cost efficiency. The study highlights the importance of inventory management in bridging cooperative long-term productivity and uncertainty, an area still underexplored in operations research.